Tamoxifen suppresses paclitaxel-, vincristine-, and bortezomib-induced neuropathy via inhibition of the protein kinase C/extracellular signal-regulated kinase pathway - Masanobu Tsubaki; Tomoya Takeda; Mikihiro Matsumoto; Natsuki Kato; Shota Yasuhara; Yu-ichi Koumoto; Motohiro Imano; Takao Satou; Shozo Nishida (Tumor Biology)
Chemotherapy-induced neuropathy is a highly problematic, dose-limiting effect of potentially curative regimens of cancer chemotherapy. When neuropathic pain is severe, patients often either switch to less-effective chemotherapy agents or choose to discontinue chemotherapy entirely. Conventional chemotherapy drugs used to treat lung and breast cancer, multiple myeloma, and lymphoma include paclitaxel, vincristine, and bortezomib. Approximately 68% of patients receiving these anticancer drugs develop neuropathy within the first month of treatment, and while strategies to prevent chemotherapy-induced neuropathy have been investigated, none have yet been proven as effective. Recent reports suggest that chemotherapy-induced neuropathy is associated with signal transduction molecules, including protein kinase C and mitogen-activated protein kinases. It is currently unclear whether protein kinase C inhibition can prevent chemotherapy-induced neuropathy. In this study, we found that tamoxifen, a protein kinase C inhibitor, suppressed paclitaxel-, vincristine-, and bortezomib-induced cold and mechanical allodynia in mice. In addition, chemotherapy drugs induce neuropathy via the protein kinase C/extracellular signal-regulated kinase pathway in the spinal cord in lumbar segments 4–6 and dorsal root ganglions. In addition, tamoxifen was shown to act synergistically with paclitaxel to inhibit tumor-growth in mice injected with tumor cells. Our results indicated that paclitaxel-, vincristine-, and bortezomib-induced neuropathies were associated with the protein kinase C/extracellular signal-regulated kinase pathway in the lumbar spinal cord and dorsal root ganglions, which suggest that protein kinase C inhibitors may be therapeutically effective for the prevention of chemotherapy-induced neuropathy when administered with standard chemotherapy agents.